A New Analysis on Self-Control in Intertemporal Choice and Mediterranean Dietary Pattern - Howatt, Brian C.; Muñoz Torrecillas, María José; Cruz Rambaud, Salvador; Takahashi, Taiki (Frontiers in Public Health, 2019)
This paper completes Muñoz Torrecillas, Cruz Rambaud and Takahashi (1) results and conclusions investigating the relationship between adherence to healthy dietary habits, specifically the Mediterranean Diet (hereinafter, MD), and impulsivity in intertemporal choices. Impulsivity can be defined as the strong preference for small immediate payoffs over larger delayed payoffs, and in the original study this behavior was captured by the parameter k (discount rate of the hyperbolic discount function), calculated using an automated scoring mechanism. Adherence to MD was measured by the KIDMED index and then grouped into three levels: high, medium and low. While the authors observed that individuals in the high adherence group had the shallowest discounting and individuals in the low adherence group had the steepest discounting, the data were not statistically analyzed in depth. Therefore, the purpose of the present paper is to propose a preliminary quantitative model for this relationship and evaluate its significance. Tests revealed a significant interaction between adherence to MD and magnitude of delayed rewards when predicting discount rates. Specifically, the degree to which impulsivity decreases as adherence to MD increases is strongly influenced by delayed rewards of smaller magnitude. These findings are consistent with the authors’ claims that healthy dietary habits may be closely linked with greater self-control when payoffs are small, and thus warrant further examination. The results do not indicate causality though, so future studies could also investigate the directions of this relationship as a means of developing behavioral interventions.